2018
DOI: 10.1002/med.21496
|View full text |Cite
|
Sign up to set email alerts
|

Potential lymphangiogenesis therapies: Learning from current antiangiogenesis therapies—A review

Abstract: In recent years, lymphangiogenesis, the process of lymphatic vessel formation from existing lymph vessels, has been demonstrated to have a significant role in diverse pathologies, including cancer metastasis, organ graft rejection, and lymphedema. Our understanding of the mechanisms of lymphangiogenesis has advanced on the heels of studies demonstrating vascular endothelial growth factor C as a central pro-lymphangiogenic regulator and others identifying multiple lymphatic endothelial biomarkers. Despite these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 224 publications
(401 reference statements)
0
47
0
Order By: Relevance
“…The potential benefits of anti-lymphangiogenic therapies for cancer treatment have been demonstrated in several pre-clinical cancer models, where blocking of VEGF-C and VEGF-D led to dramatic reduction in lymphatic vessel growth and metastasis formation (reviewed in Zheng et al, 2014). Moreover, several clinical studies targeting tyrosine kinase receptors including VEGFR1-3, FGFR, Tie2, C-MET and PDGFR-beta, that block both angiogenesis and lymphangiogenesis, reported increased survival of tumor bearing mice and human patients following treatment (reviewed in Duong et al, 2012;Dieterich and Detmar, 2016;Yamakawa et al, 2018).…”
Section: Therapies Targeting the Lymphatic Vasculature: Implicationsmentioning
confidence: 99%
“…The potential benefits of anti-lymphangiogenic therapies for cancer treatment have been demonstrated in several pre-clinical cancer models, where blocking of VEGF-C and VEGF-D led to dramatic reduction in lymphatic vessel growth and metastasis formation (reviewed in Zheng et al, 2014). Moreover, several clinical studies targeting tyrosine kinase receptors including VEGFR1-3, FGFR, Tie2, C-MET and PDGFR-beta, that block both angiogenesis and lymphangiogenesis, reported increased survival of tumor bearing mice and human patients following treatment (reviewed in Duong et al, 2012;Dieterich and Detmar, 2016;Yamakawa et al, 2018).…”
Section: Therapies Targeting the Lymphatic Vasculature: Implicationsmentioning
confidence: 99%
“…The studies showed that VEGF-C plays important role in tumor metastasis. Therefore, VEGF-C and its receptor VEGFR-3 have been considered as the promising therapeutic target in cancer (Yamakawa et al, 2018). Intriguingly, VEGF-C was found a potential regulator for dietary regulation of adiposity and cholesterol metabolism because it is required for intestinal lymphatic vessel maintenance and fat absorption (Nurmi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While there are currently no drugs approved which target lymphangiogenesis in cancer or other diseases, early animal studies are underway and human studies are eagerly anticipated. VEGF, epidermal growth factor receptor, fibroblast growth factor, and platelet‐derived growth factor pathways have been identified as potential targets . Similar to challenges encountered with cancer treatment, the problem with common pathways implicated in angiogenesis will need to be addressed and avoided.…”
Section: Important Considerations and Future Challengesmentioning
confidence: 99%